(untitled) (Práxis Educativa, 2020)
This article aims to understand how fundamentalist religious perspectives threaten the concept of Basic Education and, therefore, call into question the ideal of free, compulsory and secular public school, through the defense and regulation of homeschooling in Brazil. The qualitative study of bibliographic and documentary type is transversalized by contributions coming from the epistemological fields of the Sciences of Religion and Education, in order to highlight the ideological strategies undertaken by a religious-fundamentalist and neoconservative activism against rights-related themes, social rights, human rights and school secularity. The analysis indicates that home-based education is rooted in fundamentalist religious values, supported and strengthened by political parties, institutions and religious leaders aligned with the neoconservative movement that is now spreading internationally; and that a possible regulation of homeschooling will jeopardize the subjective public right to Basic Education, this right is ensured after decades of collective struggle for a free, compulsory, equal, inclusive and secular school. Keywords: Basic Education. Homeschooling. Religious fundamentalism. Neoconservatism.